Time-reversal-breaking Weyl nodal lines in two-dimensional A3C2 (A = Ti, Zr, and Hf) intrinsically ferromagnetic materials with high Curie temperature. Issue 17 (22nd April 2021) - Zhou, Feng; Liu, Ying; Kuang, Minquan; Wang, Peng; Wang, Jianhua; Yang, Tie; Wang, Xiaotian; Cheng, Zhenxiang; Zhang, Gang
Abstract : 2D A3 C2 (A = Ti, Zr, and Hf) materials are reported as new ferromagnetic materials with intrinsic magnetism and good stability. Abstract : Most materials that feature nontrivial band topology are spin-degenerate and three dimensional, strongly restricting them from application in spintronic nanodevices. Hence, two-dimensional (2D) intrinsically spin-polarized systems with rich topological elements are still in extreme scarcity. Here, 2D A3 C2 (A = Ti, Zr, and Hf) materials with the P 6̄ m 2 type structure are reported as new ferromagnetic materials with intrinsic magnetism and good stability. Unlike the Weyl nodal lines existing in nonmagnetic 2D systems, A3 C2 hosts time-reversal-breaking Weyl nodal rings (two Γ-centered, one K-centered, and one K′-centered) without spin–orbit coupling (SOC). These nodal rings still remained under SOC with magnetization along the z direction (easy magnetization axis). More interestingly, the Curie temperatures ( T C ) of A3 C2 were determined based on the Monte Carlo simulation. Ti3 C2 features an extraordinary T C (above 800 K), and those of Zr3 C2 and Hf3 C2 are above room temperature. Therefore, A3 C2 materials are excellent platforms to study magnetic Weyl nodal lines in high T C ferromagnetic 2D materials.